Managers' Perceptions of Factors Affecting Employees' Uptake of Workplace Health Promotion (WHP) Offers - Sigblad, Fanny; Savela, Maria; Okenwa Emegwa, Leah (Frontiers in Public Health, 2020)
Abstract Managers are often charged with the responsibility of overseeing Workplace health promotion (WHP) for which significant amounts of resources are laid aside yearly. While there is increasing interest by employers to include WHP policies, studies show that WHP implementation and uptake by employees still need to be improved upon. Given that managers are part of organizational decision-making and implementation of new policies, they serve as the bridge between workers and management. The aim of this study is to investigate managers’ perceptions of employees’ WHP uptake as well as challenges encountered by managers in the execution of their WHP-related tasks. Method: This study is based on a qualitative method using semi-structured interviews. Participants in the study were managers at medium and large-scale private companies in Northcentral Sweden. To ensure that participating companies are comparable in terms of structure and policy, only companies within the private sector were eligible to participate. Furthermore, only one manager per company was interviewed. A total of nineteen managers participated and the data generated were analyzed using content analysis. Results: A total of three themes and nine subthemes emerged. The first theme deals with factors at the individual level, subthemes include awareness of WHP, work-life balance, and attitudes. The second theme comprises of factors related to the WHP offer, subthemes were design of the WHP, supportive collaborators and financing of WHP. The third theme deals with organizational factors, subthemes were the nature of the organization’s operations, management as role models and resources and support for managers. Results show that most of the challenges encountered by managers in executing WHP were mostly at the organizational level. Conclusion: Addressing modifiable factors at the individual and organizational levels and those related to the WHP may improve WHP uptake among employees.